The brand gym a practical workout to gain and retain brand leadership - Taylor, David, 1964-; Nichols, David, 1967- (Chichester, U.K. : Wiley, 2010)
"This refreshingly simple, practical guide demonstrates how brand management can boost business performance. It is the ideal inspiration for creating growth in today's tough economic times. Following the template of the original version, the book consists of a programme of eight "Workouts" that will help marketers raise their own game in key areas such as insight, portfolio strategy, positioning and innovation"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Brand name products; Product management; Electronic books